2004
DOI: 10.1016/s0360-3016(04)01081-8
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations with time-dependent geometries to investigate effects of organ motion with high temporal resolution

Abstract: We present a novel method able to calculate dose with underlying time-dependent geometry. The technique allows 4D dose calculation in arbitrary time scales in a single simulation even for double-dynamic systems (e.g., time-dependent beam delivery under organ motion).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…Clinical application of dose‐warping techniques is a contentious topic as reflected by, for instance, a recent point‐counterpoint article and correspondences published by Medical Physics which raised the question, ‘Is it appropriate to “deform” dose along with deformable image registration in adaptive radiotherapy?’ (33) Although the answer is not likely to be without complexity, a number of published studies have shown the applicability of dose‐warping techniques 9 , 10 , 11 , 14 , 15 , 16 , 17 . We have previously corresponded to the point‐counterpoint article 34 , 35 following earlier work in which we demonstrated an experimental validation of the dose‐warping technique, as well as accurate performance of deformable registration algorithms (13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical application of dose‐warping techniques is a contentious topic as reflected by, for instance, a recent point‐counterpoint article and correspondences published by Medical Physics which raised the question, ‘Is it appropriate to “deform” dose along with deformable image registration in adaptive radiotherapy?’ (33) Although the answer is not likely to be without complexity, a number of published studies have shown the applicability of dose‐warping techniques 9 , 10 , 11 , 14 , 15 , 16 , 17 . We have previously corresponded to the point‐counterpoint article 34 , 35 following earlier work in which we demonstrated an experimental validation of the dose‐warping technique, as well as accurate performance of deformable registration algorithms (13) .…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to contend with organ deformation in image‐guided and adaptive radiotherapy often involve the implementation of deformable image registration (DIR) algorithms 4 , 5 , 6 , 7 , 8 . One approach for calculation of cumulative doses in moving and deforming targets for both inter‐ and intrafraction effects is via the ‘dose‐warping’ technique, using DIR to redistribute dose before summation 9 , 10 , 11 . Our previous work has demonstrated experimentally (using a deformable, three‐dimensional, dose‐integrating tissue‐equivalent dosimeter, ‘DEFGEL’ (12) ) that this can be performed accurately (13) when optimized appropriately.…”
Section: Introductionmentioning
confidence: 99%
“…5 One approach for the calculation of accumulated dose in different phases of the breathing cycle is via ''dose warping.'' [6][7][8][9][10][11] In previous work, we have demonstrated that this may be performed accurately 12 using the DEFGEL dosimetry system. 13 This deformable image registration-based approach revealed that conventional 3-dimensional (3D) planning approaches can significantly underestimate the dose to the planning target volume (PTV) in liver SBRT.…”
Section: Introductionmentioning
confidence: 99%
“…In such an approach, a single free‐breathing CT dataset is replaced by a series of up to 10 CT datasets sampled during various phases of a respiratory cycle. ( 10 , 14 ) However, evidence suggests that the true anatomic relationships between 4D CT image frames are uncertain, and current image‐processing methods suffer from considerable artifacts. ( 18 , 19 ) In addition, because the field size of a typical CT scan is limited, the interlinked motions and deformations involving several organs (such as heart, lungs, liver, etc.)…”
Section: Introductionmentioning
confidence: 99%